The Volatility of Stock Market in Indonesia During Covid-19 Crisis : Evidence from Consumer Goods Industry - Alghifary, Muhammad Syauqy; Ekawaty, Marlina; Sumantri, Vietha Devia Sagita (AIBPM Publisher, 2023)
This study aims to measure the volatility of stock in consumer goods industry. The analysis in this study utilize index value of consumer goods sectoral stock in 260 days. Using the paired t-test, it was discovered that stock index of consumer goods has significant change after the announcement of Covid-19 first case in Indonesia. The volatility of stock index was raised during the pandemic as measured from its standard deviation. Furthermore, the estimation of GARCH model revealed that consumer goods stock experienced a great volatility during Covid-19 crisis. The value of volatility persistence is 0,917 or close to 1, it means that the volatility was long-lasting as long as the economic crisis. The result of study could give the information for stock investor to be careful with their investment fund during the crisis. Meanwhile, the consumer goods companies can observe this result as consideration in determining the effective strategy in managing the company’s finances in the midst of an economic crisis.